2011
DOI: 10.4274/turkderm.45.09
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Side Effects of Isotretinoin in 150 Patients with Acne Vulgaris

Abstract: ÖzetAmaç: ‹zotretinoin akne tedavisinde yayg›n olarak kullan›lan, çok etkili bir tedavidir. Pek çok sistemi etkileyen çeflitli yan etkileri bulunmaktad›r. Günümüzde bu yan etkilerle ilgili sürekli yeni olgu bildirimleri yap›lmakta ve uzun dönem sonuçlar›na dair yeteri kadar çal›flma bulunmamaktad›r. Bu çal›flmada izotretinoine ba¤l› ortaya ç›kan klinik ve laboratuvar yan etkiler ve tedavi sonuçlar› de¤erlendirilmektedir. Gereç ve Yöntem: Çal›flmaya Deri ve Zührevi Hastal›klar poliklini¤ine baflvuran 150 orta v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 13 publications
0
12
0
1
Order By: Relevance
“…Our findings confirm that adverse cutaneous and mucous membrane reactions may be seen during isotretinoin therapy, and these were observed in the great majority of patients. Such reactions and poor tolerance of them have been reported by a number of previous studies (3,5,7,17,18). We therefore recommend that patients be given suitable skin care instructions during isotretinoin therapy.…”
Section: Discussionmentioning
confidence: 65%
“…Our findings confirm that adverse cutaneous and mucous membrane reactions may be seen during isotretinoin therapy, and these were observed in the great majority of patients. Such reactions and poor tolerance of them have been reported by a number of previous studies (3,5,7,17,18). We therefore recommend that patients be given suitable skin care instructions during isotretinoin therapy.…”
Section: Discussionmentioning
confidence: 65%
“…Previous researches have highlighted the harmful adverse effects of isotretinoin treatment [20] . Many undesired effects including sparse hair and hair thinning, conjunctivitis, mucous dryness and sensitivity to ultraviolet radiation [21] . Isotretinoin reduces sebaceous gland surface area and suppresses sebum production by in inhibiting sebaceous lipid synthesis [22] .…”
Section: Discussionmentioning
confidence: 99%
“…53 Iso is also known to be a potent teratogen and one of the presumed mechanisms of Iso teratogenesis is production of toxic ROS. [24][25][26]55 It has been shown that incubation of neural crest cell culture with Iso evokes an increased release of ROS. 25 Similarly, in another study it has been suggested that because Iso is metabolized by prostaglandin synthase to a toxic peroxyl radical, a prostaglandin synthetase inhibitor, acetylsalicylic acid may emerge as an anti-teratogenic agent.…”
Section: Discussionmentioning
confidence: 99%